Preliminary results from the project ”Slow On the Bottle – Enjoy the Road (SOBER)”: Instruments to measure implicit associations towards drunk- driving and to change implicit drunk-driving associations - MArtinussen, Laila M.; Sømhovd, Mikael J. (Proceedings from the Annual Transport Conference at Aalborg University, 2017)
Attitude-based interventions are often a key element in attempts to change behavior, but do not always have the expected effect. A reason for the lack of success may be that people have two types of attitudes, explicit (introspectively accessible, what people say they mean) and implicit attitudes (not accessible to conscious introspection, cannot be measured by questionnaires, but by other experiments methods). Implicit attitudes are assessed by measuring participants implicit associations between a target category (here drunk-driving and sober-driving) and valence categories (here good and bad words). International research shows that a person’s implicit associations’ sensitivity can be changed by relatively simple behavioral methods. This study aims to adjust existing methods of implicit associations’ measurement and of implicit associations change, to measure and change implicit associations towards drunk-driving. As a first step, implicit associations towards drunk-driving and sober-driving were measured with the Go/No-Go Associations Task (GNAT), and the implicit associations change was performed with behavioral training method, the Avoid/Approach Task (AAT). The preliminary results show that the GNAT successfully measures implicit associations towards drunk-driving and sober-driving. Also, the preliminary results show that the implicit associations towards drunk-driving and sober-driving were changed with the AAT. The results are promising as it looks like both instruments are applicable. The study has both national and international value, as the first study that measures implicit attitudes towards drunk-driving and also the first to try to change drunk-driving implicit attitudes. Pending a complete sample and further analysis, the results will reveal drunk-driving attitudes and if these attitudes can be changed in a socially beneficial ways.